Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

The Demand for Voluntary Carbon Dioxide Removal – Experimental Evidence from an Afforestation Project in Germany - Bartels, Lara; Kesternich, Martin; Löschel, Andreas (Land Economics)
Keywords: General Earth and Planetary Sciences; General Environmental Science

A Validation Study of the German Versions of the Feeling Scale and the Felt Arousal Scale for a Passive Relaxation Technique (Autogenic Training) - Thorenz, Kristin; Berwinkel, Andre; Weigelt, Matthias (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Housing Situations and Local COVID-19 Infection Dynamics – A Case Study With Small-Area Data - Freise, Diana; Schiele, Valentin; Schmitz, Hendrik
Keywords: General Earth and Planetary Sciences; General Environmental Science

ElectricGrid.jl - A Julia-based modeling and simulationtool for power electronics-driven electric energy grids - Wallscheid, Oliver; Peitz, Sebastian; Stenner, Jan; Weber, Daniel; Boshoff, Septimus; Meyer, Marvin; Chidananda, Vikas; Schweins, Oliver (Journal of Open Source Software)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Kompetenzentwicklung in der Lehrkräftebildung: der Mehrwert einer digitalen Simulation - Grotegut, Lea; Klingsieck, Katrin B. (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Förderung diagnostischer Kompetenz in der Lehrer*innenbildung birgt zwei Herausforderungen: Erstens bleibt in großen Lehrveranstaltungen wenig Raum für die notwendige Anwendung theoretischen Wissens, zweitens können Fehlentscheidungen in realen diagnostischen Situationen gravierende negative Folgen für Schüler*innen haben. Eine digitale Simulation kann beiden Herausforderungen begegnen. In diesem Beitrag wurde eine digitale, problemorientierte Simulation zur Förderung diagnostischer Kompetenz von Lehramtsstudierenden evaluiert und mit einer textbasierten, problemorientierten und einer lehrendenzentrierten Kontrollgruppe verglichen. Die Ergebnisse zeigen positive Effekte für die digitale Simulation hinsichtlich der selbstbestimmten Motivation, aber einen geringeren Wissenszuwachs im Vergleich zum lehrendenzentrierten Setting. Die Selbstwirksamkeit nahm in allen drei Gruppen zu. Eine digitale Simulation bietet in der untersuchten Form somit einen, wenn auch geringen, Mehrwert für die Lehrkräftebildung im Bereich der Kompetenzentwicklung.
Keywords: General Earth and Planetary Sciences; General Engineering; General Environmental Science

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

Implications of Algorithmic Wage Setting on Online Labor Platforms: a Simulation-Based Analysis∗ - Dawid, Herbert; Harting, Philipp; Neugart, Michael (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Recalibration of limits to growth: An update of the World3 model - Nebel, Arjuna; Kling, Alexander; Willamowski, Ruben; Schell, Tim (Journal of Industrial Ecology)
Abstract After 50 years, there is still an ongoing debate about the Limits to Growth (LtG) study. This paper recalibrates the 2005 World3‐03 model. The input parameters are changed to better match empirical data on world development. An iterative method is used to compute and optimize different parameter sets. This improved parameter set results in a World3 simulation that shows the same overshoot and collapse mode in the coming decade as the original business as usual scenario of the LtG standard run. The main effect of the recalibration update is to raise the peaks of most variables and move them a few years into the future. The parameters with the largest relative changes are those related to industrial capital lifetime, pollution transmission delay, and urban‐industrial land development time.
Keywords: General Social Sciences; General Environmental Science